ETHISCHE ASPEKTE IN DER ARBEIT VON BIOMEDIZINERN (CIPEEX, 2025)
The role of biomedical professionals has expanded into various areas of healthcare, such as clinical analysis,diagnostic imaging, aesthetics, extracorporeal perfusion, exercise physiology, genetic counseling, and gerontology, among others. With this growth, it has become essential to understand the ethical aspects involved in the practice. The objective of this study was to analyze the main ethical elements related to the work of biomedical professionals, with an emphasis on professional competencies, ethical and legal limits, and clinical impacts.Methodology: A narrative review of the literature was conducted in databases such as PubMed and Google Scholar, with articles from the last 10 years published in English and Portuguese in full version.Clinical studies addressing the topic were included, excluding duplicate publications and those deviating from the topic. The studies analyzed address the training, legal duties, and regulatory requirements of the profession, as established by the Federal Council of Biomedicine (CFBM) and current legislation, as well as by the Regional Council of Biomedicine, union, and associations. The results indicate that, despite the variety of areas of practice, biomedical professionals must respect their technical and ethical limits, in addition to seeking constant scientific updating and technical mastery.The importance of working in a multidisciplinary team to ensure quality in health care is also highlighted. It is concluded that understanding medical aspects is essential for patient safety.